Lithium ion secondary battery and electric device
By using a double-layer negative electrode active material layer structure composed of graphite primary particles and secondary particles in a lithium-ion secondary battery, the problem of insufficient fast charging performance of existing lithium-ion secondary batteries is solved, and high energy density and excellent fast charging performance are achieved.
Patent Information
- Application Number
- CN202510018184.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The existing lithium-ion secondary batteries have insufficient performance during fast charging and discharging, and the fast charging performance needs to be further improved.
A double-layer negative electrode active material layer structure is adopted, wherein the first negative electrode active material layer is composed of graphite primary particles and the second negative electrode active material layer is composed of graphite secondary particles. The two are laminated in a specific proportion to improve the detachment efficiency of lithium ions.
It realizes excellent performance of lithium-ion secondary batteries in the fast charging and discharging process, and has high energy density and good fast charging performance.
Smart Images

Figure CN119890410A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular, to lithium-ion secondary batteries and electrical devices. Background Art
[0002] Secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles and electric vehicles. With the gradual expansion of the scope of battery applications, the market has also put forward higher requirements for the rapid charging and discharging capabilities of batteries. However, the current batteries still have many deficiencies in the application process, and the fast charging performance of batteries needs to be further improved.
[0003] It should be noted that the above statements are only used to provide background technical information related to the present application and do not necessarily constitute prior art. Summary of the invention
[0004] In the first aspect of the present application, the present application proposes a lithium-ion secondary battery, including a negative electrode plate, the negative electrode plate including: a negative current collector; a negative active material layer, the negative active material layer including a first negative active material layer and a second negative active material layer stacked, the second negative active material layer being located on a side of the first negative active material layer away from the negative current collector, wherein the first negative active material layer includes a first negative active material, the first negative active material includes graphite, and the number of primary particles in the first negative active material accounts for a greater proportion than the number of secondary particles; the second negative active material layer includes a second negative active material, the second negative active material includes graphite, and the number of secondary particles in the second negative active material accounts for a greater proportion than the number of primary particles. As a result, the lithium-ion secondary battery has both excellent fast charging performance and high energy density.
[0005] In some embodiments, the amount of primary particles in the first negative electrode active material accounts for greater than or equal to 70%, and the oil absorption value of the first negative electrode active material is 45mL / 100g-60mL / 100g. Thus, the specific capacity of the negative electrode sheet can be increased.
[0006] In some embodiments, the amount of secondary particles in the second negative electrode active material accounts for greater than or equal to 70%, and the oil absorption value of the second negative electrode active material is greater than the oil absorption value of the first negative electrode active material. Thus, the lithium-ion secondary battery has better fast charging performance.
[0007] In some embodiments, the oil absorption value of the second negative electrode active material is 47 mL / 100 g-62 mL / 100 g.
[0008] In some embodiments, the Dv50 particle size of the second negative electrode active material is smaller than the Dv50 particle size of the first negative electrode active material. Thus, there are more pores in the second negative electrode active material layer, which is conducive to the infiltration of the electrolyte into the negative electrode sheet.
[0009] In some embodiments, the Dv50 particle size of the first negative electrode active material is 14 μm-22 μm, and / or the Dv50 particle size of the second negative electrode active material is 12 μm-19 μm.
[0010] In some embodiments, the thickness of the first negative electrode active material layer is H1, the thickness of the second negative electrode active material layer is H2, and the ratio of H1 to H2 is in the range of (2:3)-(4:1). This helps the lithium-ion secondary battery to have both higher energy density and better fast charging performance.
[0011] In some embodiments, H1 is 30 μm-90 μm, and H2 is 20 μm-60 μm.
[0012] In some embodiments, the specific surface area of the second negative electrode active material is greater than the specific surface area of the first negative electrode active material, thereby helping to improve the wetting of the negative electrode plate by the electrolyte.
[0013] In some embodiments, under a pressure of 50000 N, the compaction density of the first negative electrode active material is greater than the compaction density of the second negative electrode active material, thereby helping to increase the specific capacity of the negative electrode sheet.
[0014] In some embodiments, the OI value of the powder of the second negative electrode active material is less than the OI value of the first negative electrode active material, thereby helping to improve the fast charging performance of the negative electrode plate.
[0015] In some embodiments, the gram capacity of the first negative electrode active material is greater than the gram capacity of the second negative electrode active material, thereby helping to increase the specific capacity of the negative electrode sheet.
[0016] In some embodiments, the second negative electrode active material includes the secondary particle with a carbon coating layer, the carbon coating layer is located at least on a portion of the surface of the secondary particle, the secondary particle is formed by bonding at least two primary particles, and the bonding material includes a carbon material. This helps to improve the fast charging performance of the negative electrode plate.
[0017] In some embodiments, the compaction density of the negative electrode active material layer is 1.65 g / cm 3 -1.85g / cm 3 This helps to improve the wetting of the negative electrode sheet by the electrolyte.
[0018] In the second aspect of the present application, the present application proposes an electric device, comprising the aforementioned lithium-ion secondary battery. Therefore, the electric device has all the characteristics and advantages of the aforementioned battery, which will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0020] Figure 1 This is a schematic diagram of the structure of a negative electrode sheet according to an embodiment of the present application;
[0021] Figure 2 is a schematic diagram of a battery cell according to an embodiment of the present application;
[0022] Figure 3 yes Figure 2 An exploded view of a battery cell according to an embodiment of the present application is shown;
[0023] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application;
[0024] Figure 5 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0025] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0026] Figure 7 is a schematic diagram of an electrical device according to an embodiment of the present application;
[0027] Figure 8 It is a scanning electron microscope image of the negative electrode active material containing secondary particles.
[0028] Description of reference numerals:
[0029] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell;
[0030] 51 housing; 52 electrode assembly; 53 top cover assembly;
[0031] 100 negative electrode current collector; 110 first negative electrode active material layer; 120 second negative electrode active material layer. DETAILED DESCRIPTION
[0032] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0033] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0034] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0035] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.
[0036] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0037] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.
[0038] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0039] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0040] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0041] The technical features in this application can be tested by reverse disassembling the battery, or by obtaining fresh materials during battery preparation / batteries that have not been shipped out of the factory. For example, when testing the characteristics of the negative electrode active material, the graphite powder obtained by scraping and burning the negative electrode sheet after disassembling the battery can be tested, or fresh graphite that has not been made into a battery can be obtained for testing.
[0042] Taking graphite as an example, the structure of the negative electrode active material is more stable, especially under high compaction density, it can still ensure good structural stability. And because the graphite primary particles are not agglomerated, it is easier to disperse evenly during the mixing process of the negative electrode slurry, which is manifested as a lower oil absorption value. The primary particles have fewer concave and convex structures on the surface, and it is easier for the particles to slip during the cold pressing process, and form a close connection with the current collector, which is manifested as high compaction and high cell volume energy density. However, since the graphite primary particles are anisotropic, lithium ions can only be embedded in the interlayer structure of graphite along the end face of graphite, resulting in a low lithium ion migration rate of graphite, and the expansion force generated by the lithium ions embedded in the interlayer structure of graphite can only be released in the direction perpendicular to the interlayer structure, which makes the thickness of the negative electrode sheet change greatly during the charge and discharge process, and the battery expands more obviously, which is easy to cause the electrolyte generated by the expansion of the negative electrode sheet to be squeezed out and unable to flow back, and then cause the battery cycle to dive.
[0043] Unlike graphite primary particles, graphite secondary particles are isotropic. The more lithium ion transmission channels in the secondary particles can effectively increase the lithium ion insertion and extraction entrances of the negative electrode active material, improve the lithium ion interface reaction, increase the migration rate of lithium ions, and then improve the fast charging performance of the negative electrode active material. At the same time, the expansion force generated during the lithium insertion process can be released in multiple directions, thereby reducing the thickness change of the negative electrode plate during the charging and discharging process, and the battery expansion is correspondingly reduced, which can effectively alleviate the electrolyte being squeezed out and unable to flow back due to the expansion of the negative electrode plate. Furthermore, the secondary particles are formed by the bonding of primary particles, and more concave-convex structures will be formed between the particles. The concave-convex structure has a strong adsorption of the dispersant, and a large amount of the dispersant in the negative electrode slurry will be adsorbed on the particle surface, so that the lithium insertion and extraction channels on the graphite surface are blocked, and there is less free dispersant in the negative electrode slurry. The stability of the negative electrode slurry is poor. At this time, the negative electrode active material exhibits a higher oil absorption value. In order to compensate for the excessive adsorption of dispersant by negative electrode active materials with larger oil absorption values and achieve uniform dispersion of negative electrode slurry, more dispersant needs to be added to the negative electrode slurry. However, since the dispersant itself does not have the function of inserting and extracting lithium, the proportion of negative electrode active materials that can provide lithium insertion and extraction sites in the negative electrode slurry will decrease, and the proportion of negative electrode active materials in the negative electrode active material layer formed by coating the negative electrode slurry will decrease accordingly, ultimately resulting in a lower specific capacity of the negative electrode active material layer.
[0044] In the present application, a first negative electrode active material and a second negative electrode active material are used in combination to form a negative electrode active material layer, wherein the first negative electrode active material and the second negative electrode active material both include graphite, the number of primary particles in the first negative electrode active material accounts for a greater proportion than the number of secondary particles, and the number of secondary particles in the second negative electrode active material accounts for a greater proportion than the number of primary particles.
[0045] Specifically, in a double-layer or multi-layer negative electrode active material system, the second negative electrode active material is closer to the electrolyte, and the surrounding ion concentration is higher, making it easier for ions to accumulate and cause lithium precipitation. Therefore, when the number of secondary particles in the second negative electrode active material is relatively large compared to the number of primary particles, the secondary particles can use more lithium insertion and extraction channels to ensure that lithium ions are quickly transferred to the particle body, improve the lithium ion interface reaction, and increase the migration rate of lithium ions, thereby improving the fast charging performance of the second negative electrode active material. However, the secondary particles have more end faces and fewer lithium storage sites, and the concave and convex surface of the secondary particles makes it difficult for the particles to slip during the cold pressing process, and the compaction density is low, which affects the volume energy density of the negative electrode sheet. Therefore, the second negative electrode active material layer has higher kinetic performance and relatively lower gram capacity. Furthermore, in a double-layer or multi-layer negative electrode active material layer system, the first negative electrode active material is closer to the negative electrode current collector, the surrounding ion concentration is relatively low, and the requirement for lithium ion migration rate is relatively low. When the number of primary particles in the first negative electrode active material is higher than that of secondary particles, the first negative electrode active material layer can make full use of the characteristics of primary particles with large gram capacity, easier compaction, lower oil absorption value, and less dispersant required in the negative electrode slurry, so that the number of active materials with high gram capacity in the first negative electrode active material layer is high, which greatly improves the overall specific capacity of the negative electrode sheet and makes up for the low specific capacity of the second negative electrode active material layer. Through the combination of the first negative electrode active material and the second negative electrode active material, the lithium-ion secondary battery has both excellent fast charging performance and high energy density.
[0046] Specifically, during the charge and discharge process of the battery, lithium ions are released from the positive electrode active material and first embedded in the second negative electrode active material layer located on the outside of the negative electrode plate. Since the number of secondary particles in the second negative electrode active material accounts for a relatively high proportion, it is helpful for the rapid embedding of lithium ions. The negative electrode plate has excellent fast charging performance during the charge and discharge process, which helps to meet the battery's usage requirements in fast charging scenarios. Furthermore, after the lithium ions are embedded in the second negative electrode active material layer, they will continue to migrate to the first negative electrode active material layer. Since the first negative electrode active material layer has a higher specific capacity, it can provide more lithium embedding sites, thereby helping to embed lithium ions in the first negative electrode active material layer as much as possible, effectively reducing the occurrence of lithium dendrites on the surface of the negative electrode plate, and improving the fast charging performance and specific capacity of the negative electrode plate.
[0047] In the present application, "the number ratio of secondary particles in the negative electrode active material can be determined by scanning electron microscopy. As an example, the test method for the number ratio of secondary particles can be: the negative electrode active material is evenly laid and adhered to the conductive glue to form a sample to be tested with a length × width = 6 cm × 1.1 cm; the particle morphology is tested using a scanning electron microscope (such as ZEISS Sigma 300). The test can refer to JY / T010-1996. In order to ensure the accuracy of the test results, multiple (for example, 20) different areas can be randomly selected from the sample to be tested for scanning testing, and at a certain magnification (for example, 1000 times), the percentage of the number of secondary particles in each test area to the total number of particles is calculated, that is, the number ratio of secondary particles in the area, and the average value of the test results of the corresponding multiple (for example, 20) test areas is taken as the number ratio of secondary particles in the negative electrode active material.
[0048] It should be noted that, in the present application, the percentage of the number of primary particles in the negative electrode active material (%) + the percentage of the number of secondary particles in the negative electrode active material = 100%.
[0049] The first negative electrode active material layer and the second negative electrode active material layer have different compaction densities due to different material compositions. For example, when the compaction density of the first negative electrode active material layer is greater than the compaction density of the second negative electrode active material layer, since the compaction density of the negative electrode active material layer is related to the stacking structure of the negative electrode active material layer, at this time, the overall structure of the second negative electrode active material layer is looser than that of the first negative electrode active material layer. Therefore, the first negative electrode active material layer and the second negative electrode active material layer can be distinguished in the following manner to obtain the first negative electrode active material and the second negative electrode active material.
[0050] Specifically: ① Use ceramic scissors to cut the negative electrode into 6mm×6mm size, stick it on the sample stage coated with paraffin, and make the sample slightly protrude (<1mm) from the edge of the sample stage, and then polish the cross section and slice it; ② Put the slice on the CP-SEM (Cross Section Polisher-Scanning Electron Microscope), that is, cross-section polishing-scanning electron microscope cavity, adopt backscattering mode, take more than 10 scanning pictures at 1000 times, test the thickness of the negative electrode sheet, and perform porosity analysis on the scanning pictures with a step length of 10μm thickness. The area where the porosity changes significantly is defined as the interface between the first negative electrode active material layer and the second negative electrode active material layer. The distance between the test interface layer and the copper foil is the thickness of the first negative electrode active material layer H1, and the thickness of the second negative electrode active material layer H2 is the thickness of the entire electrode sheet H minus the thickness of the first negative electrode active material layer H1; ③ The powder scraped off from the surface of the negative electrode sheet with a thickness of two-thirds of H2 is defined as the second negative electrode active material, and the remaining negative electrode sheet is continued to be scraped. During the scraping process, a micrometer or a laser thickness gauge is used to measure the remaining thickness of the negative electrode sheet for testing until the thickness of the remaining negative electrode active material layer is 2 / 3 of H1, and the powder in this area is defined as the first negative electrode active material; ④ The aforementioned first negative electrode active material powder and the second negative electrode active material are tested for the proportion of secondary particles. For example, the number ratio of secondary particles can be calculated as follows: (a) The aforementioned negative electrode active material powder is evenly dispersed on a conductive tape substrate by vacuum negative pressure spraying; (b) A scanning electron microscope (such as ThermoScientific Apreo 2S) mapping function is used to take 50 pictures at 500 times magnification at high speed; (c) The particles in each picture are automatically marked using an AI deep learning model or manual image recognition to obtain the number of primary and secondary particles, and the results are statistically analyzed to calculate the number ratio of secondary particles. Among them, a secondary particle is defined as: when two or more particles are stacked, they are regarded as a secondary particle. For example, a secondary particle can be a stack of multiple particles with different particle sizes (see Figure 8 ① in the figure), multiple particles with similar particle sizes are stacked (see Figure 8 ② in the above), multiple small particles stacked on the surface of a large particle (see Figure 8 ③ in ). Primary particles are defined as particles that are not stacked. For example, see Figure 8 ④ and ⑤ in the above.
[0051] In the first aspect of the present application, reference is made to Figure 1The present application proposes a lithium-ion secondary battery, including a negative electrode plate, the negative electrode plate including: a negative electrode collector 100; a negative electrode active material layer, the negative electrode active material layer including a first negative electrode active material layer 110 and a second negative electrode active material layer 120 which are stacked, the second negative electrode active material layer 120 being located on a side of the first negative electrode active material layer 110 away from the negative electrode collector 100, wherein the first negative electrode active material layer 110 includes a first negative electrode active material; the first negative electrode active material includes graphite, and the number of primary particles in the first negative electrode active material accounts for a greater proportion than the number of secondary particles; the second negative electrode active material layer 120 includes a second negative electrode active material, the second negative electrode active material includes graphite, and the number of secondary particles in the second negative electrode active material accounts for a greater proportion than the number of primary particles. The first negative electrode active material layer can provide more lithium insertion sites, thereby improving the specific capacity of the negative electrode plate, and the second negative electrode active material layer can provide more rapid lithium insertion and extraction channels, thereby improving the fast charging performance of the negative electrode plate. Therefore, lithium-ion secondary batteries have both excellent fast charging performance and high energy density.
[0052] In some embodiments, the amount of primary particles in the first negative electrode active material accounts for greater than or equal to 70%, and the oil absorption value of the first negative electrode active material is 45 mL / 100 g-60 mL / 100 g.
[0053] As an example, the amount of primary particles in the first negative electrode active material may account for 70%, 75%, 80%, 85%, 90%, 95% or 100%.
[0054] As an example, the oil absorption value of the first negative electrode active material can be 45mL / 100g, 46mL / 100g, 47mL / 100g, 48mL / 100g, 49mL / 100g, 50mL / 100g, 51mL / 100g, 52mL / 100g, 53mL / 100g, 54mL / 100g, 55mL / 100g, 56mL / 100g, 57mL / 100g, 58mL / 100g, 59mL / 100g or 60mL / 100g.
[0055] For the first negative electrode active material, the greater the proportion of primary particles in the first negative electrode active material, the greater the gram capacity of the first negative electrode active material. When the first negative electrode active material is composed entirely of primary particles, the first negative electrode active material has the most lithium insertion sites, and the gram capacity of the first negative electrode active material is optimal. At the same time, the oil absorption value of the first negative electrode active material is also low, and less dispersant is required when dispersed in the negative electrode slurry, and the specific capacity of the formed first negative electrode active material layer is also improved. At this time, lithium ions can only be inserted and removed from the end face of the first negative electrode active material, so the first negative electrode active material has a higher gram capacity and relatively poor kinetic performance. Those skilled in the art can select the primary particle proportion and oil absorption value of the first negative electrode active material according to actual conditions.
[0056] In some embodiments, the amount of secondary particles in the second negative electrode active material accounts for greater than or equal to 70%, and the oil absorption value of the second negative electrode active material is greater than the oil absorption value of the first negative electrode active material.
[0057] As an example, the amount of the secondary particles in the second negative electrode active material may account for 70%, 75%, 80%, 85%, 90%, 95% or 100%.
[0058] In some embodiments, the oil absorption value of the second negative electrode active material is 47 mL / 100 g-62 mL / 100 g.
[0059] As an example, the oil absorption value of the second negative electrode active material can be 47mL / 100g, 48mL / 100g, 49mL / 100g, 50mL / 100g, 51mL / 100g, 52mL / 100g, 53mL / 100g, 54mL / 100g, 55mL / 100g, 56mL / 100g, 57mL / 100g, 58mL / 100g, 59mL / 100g, 60mL / 100g, 61mL / 100g or 62mL / 100g.
[0060] The number of secondary particles in the second negative electrode active material accounts for a higher proportion than the number of secondary particles in the first negative electrode active material. The surface of the secondary particles will expose more concave and convex surfaces, and the oil absorption value is larger. More dispersants are required to maintain dispersion, which in turn causes the lithium insertion and extraction channels to be covered, affecting ion transmission. The second negative electrode active material has a larger oil absorption value than the first negative electrode active material. When the oil absorption value of the second negative electrode active material is in the range of 47mL / 100g-62mL / 100g, the secondary particles can be processed using less dispersant, thereby balancing the dynamics. Therefore, when the oil absorption value of the secondary particles is limited to a specific range, the negative electrode active material requires less dispersant to be processed, and the lithium insertion end face is more exposed, achieving a balance between processing and dynamics.
[0061] It is understandable that, for the second negative electrode active material, the greater the proportion of secondary particles in the second negative electrode active material, the better the kinetics of the second negative electrode active material. When the second negative electrode active material is composed entirely of secondary particles, the kinetics of the second negative electrode active material is optimal. At this time, the second negative electrode active material is mainly composed of secondary particles, so that it has more end faces and fewer lithium storage sites. Therefore, the second negative electrode active material has higher kinetics and relatively lower gram capacity. Furthermore, at this time, the oil absorption value of the second negative electrode active material is also higher, and there are more concave and convex surfaces, which makes it more difficult to press during the cold pressing process, and the volume energy density of the battery is reduced. Those skilled in the art can select the proportion of the number of secondary particles and the oil absorption value of the second negative electrode active material according to actual conditions.
[0062] In the present application, the "oil absorption value of the negative electrode active material" can be obtained according to the amount of dibutyl phthalate used when the mixture of the negative electrode active material and dibutyl phthalate changes from a free-flowing state to a semi-plastic agglomerate. Specifically, 100 g of the negative electrode active material is placed in the feed port of the oil absorption value tester, and dibutyl phthalate is automatically titrated to the negative electrode active material through the equipment until the negative electrode active material becomes a semi-plastic agglomerate. The amount of dibutyl phthalate added at this time (a mL) is recorded, so as to obtain the oil absorption value of the negative electrode active material as a mL / 100 g.
[0063] The first negative electrode active material layer and the second negative electrode active material layer have different compaction densities due to different material compositions. For example, when the compaction density of the first negative electrode active material layer is greater than the compaction density of the second negative electrode active material layer, since the compaction density of the negative electrode active material layer is related to the stacking structure of the negative electrode active material layer, at this time, the overall structure of the second negative electrode active material layer is looser than that of the first negative electrode active material layer. Therefore, the first negative electrode active material layer and the second negative electrode active material layer can be distinguished in the following manner to obtain the first negative electrode active material and the second negative electrode active material.
[0064] Specifically: ① Use ceramic scissors to cut the negative electrode into 6mm×6mm size, stick it on the sample stage coated with paraffin, and make the sample slightly protrude (<1mm) from the edge of the sample stage, and then polish the cross section and slice it; ② Put the slice on the CP-SEM (Cross Section Polisher-Scanning Electron Microscope), that is, cross-section polishing-scanning electron microscope cavity, adopt backscattering mode, take more than 10 scanning pictures at 1000 times, test the thickness of the negative electrode sheet, and perform porosity analysis on the scanning pictures with a step length of 10μm thickness. The area where the porosity changes significantly is defined as the interface between the first negative electrode active material layer and the second negative electrode active material layer. The distance between the test interface layer and the copper foil is the thickness of the first negative electrode active material layer H1, and the thickness of the second negative electrode active material layer H2 is the overall thickness of the electrode sheet H minus the thickness of the first negative electrode active material layer H1; ③ The powder of two-thirds of the thickness of H2 scraped off from the surface of the negative electrode sheet is defined as the second negative electrode active material, and the remaining negative electrode sheet is continued to be scraped until the thickness of the remaining negative electrode active material layer is 2 / 3 of H1, and the powder in this area is defined as the first negative electrode active material; ④ The aforementioned first negative electrode active material powder and the second negative electrode active material are tested for oil absorption value respectively.
[0065] In some embodiments, the Dv50 particle size of the second negative electrode active material is smaller than the Dv50 particle size of the first negative electrode active material. Therefore, the second negative electrode active material is more difficult to press during the cold pressing process, and the formed film layer has more pores, which is conducive to the infiltration of the electrolyte into the negative electrode sheet.
[0066] In some embodiments, the Dv50 particle size of the first negative electrode active material is 14 μm-22 μm, and / or the Dv50 particle size of the second negative electrode active material is 12 μm-19 μm.
[0067] The aforementioned Dv50 particle size refers to the particle size corresponding to when the cumulative volume distribution percentage of the particles reaches 50%.
[0068] The "particle size" of the present application can be measured by laser diffraction particle size analysis. Specifically, the particle size of the negative electrode active material can be measured with reference to the standard GB / T 19077-2016 using a laser particle size analyzer (eg, Malvern Master Size 3000).
[0069] In some embodiments, the thickness of the first negative electrode active material layer is H1, the thickness of the second negative electrode active material layer is H2, and the ratio of H1 to H2 is in the range of (2:3)-(4:1). This helps the negative electrode plate to have both a higher specific capacity and better fast charging performance.
[0070] As examples, the ratio of H1 to H2 may be 2:3, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, or 4:1.
[0071] When the ratio of H2 to H1 is within the above range, the negative electrode sheet has better fast charging performance, lower volume expansion rate and higher specific capacity. Among them, the first negative electrode active material layer can effectively improve the specific capacity of the negative electrode sheet, and the second negative electrode active material layer can take into account both improving the fast charging performance and inhibiting the expansion of the negative electrode sheet.
[0072] In some embodiments, H1 is 30 μm-90 μm, and H2 is 20 μm-60 μm.
[0073] As an example, H1 may be 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, or 90 μm.
[0074] As an example, H2 may be 20 μm, 30 μm, 40 μm, 50 μm or 60 μm.
[0075] In some embodiments, the specific surface area of the second negative electrode active material is greater than the specific surface area of the first negative electrode active material, thereby helping to improve the wetting of the negative electrode plate by the electrolyte.
[0076] Specific surface area refers to the surface area of an object per unit mass. The larger the specific surface area, the more channels and shorter paths for lithium ion migration, and the better the fast charging performance of the negative electrode active material. However, more dispersants are also required for dispersion, that is, when the number of secondary particles of the negative electrode active material accounts for a large proportion, the larger the specific surface area of the negative electrode active material, the greater the oil absorption value of the negative electrode active material. When the specific surface area of the second negative electrode active material is greater than that of the first negative electrode active material, the second negative electrode active material improves the fast charging performance more significantly.
[0077] As an example, the specific surface area of the first negative electrode active material may be 1.5 m 2 / g-3.5m 2 / g, for example, the specific surface area of the first negative electrode active material can be 1.5m 2 / g-2.5m 2 / g.
[0078] As an example, the specific surface area of the second negative electrode active material may be 3.0 m 2 / g-4.5m 2 / g, for example, the specific surface area of the second negative electrode active material can be 3.4m 2 / g-4.0m 2 / g.
[0079] The "specific surface area" of the negative electrode active material can be measured using the American Microelectronics multi-station fully automatic specific surface area and pore analyzer GeminiVII2390. Take about 7g of the negative electrode active material sample and put it into a 9cc long tube with a bulb, degas at 150℃ for 15min, and then put it into the host test to obtain BET data.
[0080] In some embodiments, under a pressure of 50000 N, the compaction density of the first negative electrode active material is greater than the compaction density of the second negative electrode active material, thereby helping to increase the specific capacity of the negative electrode sheet.
[0081] The higher the compaction density of the negative electrode active material powder, the easier it is to compact the negative electrode active material after rolling, which makes the specific capacity of the negative electrode active material layer higher. When the compaction density of the first negative electrode active material is greater than the compaction density of the second negative electrode active material, the first negative electrode active material layer is more compact after rolling, which can provide more lithium insertion and extraction sites for the negative electrode plate, and the overall pore structure of the negative electrode plate is still more, which is conducive to the infiltration of the electrolyte into the negative electrode plate and the insertion and extraction of lithium ions.
[0082] As an example, the powder compaction density of the first negative electrode active material at 50000N may be 1.85 g / cm 3 -2.00g / cm 3 For example, the powder compaction density of the first negative electrode active material at 50000N may be 1.88 g / cm 3 -1.98g / cm 3 .
[0083] As an example, the powder compaction density of the second negative electrode active material at 50000N may be 1.78 g / cm 3 -1.95g / cm 3 For example, the powder compaction density of the second negative electrode active material at 50000N may be 1.80 g / cm 3 -1.90g / cm 3 .
[0084] In some embodiments, the OI value of the powder of the second negative electrode active material is less than the OI value of the first negative electrode active material, thereby helping to improve the fast charging performance of the negative electrode plate.
[0085] The smaller the OI value, the stronger the lithium ion embedding ability of the negative electrode active material. Specifically, the greater the proportion of secondary particles in the negative electrode active material, the smaller the OI value of the negative electrode active material. When the powder OI value of the second negative electrode active material is less than the OI value of the first negative electrode active material, the number of secondary particles in the second negative electrode active material accounts for a large proportion. Compared with the primary particles that can only embed lithium ions from the end face, the secondary particles are isotropic and can embed lithium ions from multiple directions. The second negative electrode active material layer has the ability to quickly complete lithium ion embedding, which can effectively improve the fast charging performance of the negative electrode sheet.
[0086] As an example, the powder OI value of the first negative electrode active material may be 30-45, for example, the powder OI value of the first negative electrode active material may be 35-40.
[0087] As an example, the powder OI value of the second negative electrode active material may be 2-10, for example, the powder OI value of the second negative electrode active material may be 3-8.
[0088] When the negative electrode active material graphite is made into a negative electrode sheet, the arrangement direction (orientation) of the graphite layered structure has a great influence on the migration of lithium ions. Since only the end faces of graphite can embed and extract lithium ions, ideally, it is more beneficial for lithium ion diffusion when the end faces of graphite in the negative electrode active material are perpendicular to the surface of the negative electrode sheet, but it is difficult to accurately control the orientation of each graphite particle during actual preparation. The orientation of graphite on the negative electrode sheet can be tested by XRD. When the diffraction spectrum of the horizontally placed negative electrode sheet sample is tested, the diffraction signal of the (110) crystal plane that can be collected comes from the graphite in the negative electrode active material layer that is perpendicular to the surface of the negative electrode sheet, and the diffraction signals of the (002) and (004) crystal planes come from the graphite in the negative electrode active material whose structure is parallel to the surface of the electrode sheet. Therefore, the orientation of graphite in the negative electrode sheet can be described by the ratio of the (002) or (004) diffraction peak intensity (or integrated area) to the (110) diffraction peak intensity (or integrated area). The formula is described as: OI=I(002) / I(110) or OI=I(004) / I(110), where OI (orientation index) is the orientation of graphite in the negative electrode active material layer.
[0089] In some embodiments, the gram capacity of the first negative electrode active material is greater than the gram capacity of the second negative electrode active material. Since the second negative electrode active material is mainly composed of secondary particles, the secondary particles have more exposed end faces, but the end faces do not have a lithium storage function, so the gram capacity is relatively low. The first negative electrode active material is mainly used to increase the specific capacity of the negative electrode plate. When the gram capacity of the first negative electrode active material is greater than the gram capacity of the second negative electrode active material, the capacity provided by the first negative electrode active material layer is greater, and the negative electrode plate has a higher specific capacity.
[0090] As an example, the gram capacity of the first negative electrode active material may be greater than or equal to 358 mAh / g, for example, the gram capacity of the first negative electrode active material may be 360 mAh / g-367 mAh / g. The interior may be used for lithium insertion.
[0091] As an example, the gram capacity of the second negative electrode active material may be greater than or equal to 354 mAh / g. For example, the gram capacity of the second negative electrode active material may be 355 mAh / g-361 mAh / g.
[0092] In some embodiments, the second negative electrode active material includes the secondary particle with a carbon coating layer, the carbon coating layer is located at least on a portion of the surface of the secondary particle, the secondary particle is formed by bonding at least two primary particles, and the bonding material includes a carbon material. This helps to improve the fast charging performance of the negative electrode plate.
[0093] The carbon coating layer can cover the active sites on the surface of the graphite secondary particles, reduce the direct contact between the secondary particles in the negative electrode active material and the electrolyte, reduce the occurrence of irreversible side reactions, and restrict and buffer the volume expansion of graphite, thereby increasing stability during the cycle.
[0094] As an example, the carbon coating layer may include amorphous carbon, for example, soft carbon and / or hard carbon. The amorphous carbon coating layer has a large interlayer spacing, which helps to inhibit the expansion of the second negative electrode active material, improve the diffusion rate of lithium ions in the second negative electrode active material, enhance the large current charge and discharge capability, and improve the performance of the battery at a high rate.
[0095] It can be understood that, for the first negative electrode active material, it is mainly used to provide lithium insertion sites for the negative electrode plate, and the amorphous carbon coating layer can only improve the insertion channel of lithium ions, and it itself cannot be used as an effective lithium insertion site. Therefore, for the first negative electrode active material, in order to meet the higher gram capacity requirements, the carbon coating layer may not be set on the surface of the primary particles.
[0096] In some embodiments, the tap density of the second negative electrode active material is less than the tap density of the first negative electrode active material.
[0097] When the concavo-convex structures on the surface of the negative electrode active material particles are less, the negative electrode active materials are more closely attached to each other, have a higher tap density, and at this time, the amount of dispersant required in the negative electrode slurry is also less. Therefore, when the tap density of the first negative electrode active material is greater than the tap density of the second negative electrode active material, the particles of the first negative electrode active material are more closely attached to each other, which helps to increase the specific capacity of the first negative electrode active material layer, and then increase the specific capacity of the negative electrode sheet.
[0098] As an example, the tap density of the first negative electrode active material may be 0.95 g / cm 3 -1.30g / cm 3 For example, the tap density of the first negative electrode active material can be 1.00 g / cm 3 -1.20g / cm 3 .
[0099] As an example, the tap density of the second negative electrode active material can be 0.90 g / cm 3 -1.20g / cm 3 For example, the tap density of the second negative electrode active material can be 0.95 g / cm 3 -1.10g / cm 3 .
[0100] Tap density refers to the mass per unit volume of the powder in the container after being tapped under specified conditions, and the unit is g / cm 3 . Measured by a special tap density instrument.
[0101] It can be understood that the tap density is affected by the particle size of the material. When the particle size of the negative electrode active material meets the above definition, the tap density within the above range can be obtained.
[0102] In some embodiments, the compaction density of the negative electrode active material layer is 1.65 g / cm 3 -1.85g / cm 3 This helps to improve the wetting of the negative electrode sheet by the electrolyte.
[0103] At this compaction density, the negative electrode active material layer has more pores, the electrolyte has better infiltration into the negative electrode active material layer, and the liquid phase conduction rate of lithium ions is faster. Furthermore, when the second negative electrode active material has a surface carbon coating layer, the solid phase conduction rate of lithium ions can be further improved by the carbon coating layer, thereby improving the fast charging performance of the negative electrode plate.
[0104] The compaction density of the negative electrode active material layer mentioned above refers to the compaction density of the negative electrode active material layer after roller pressing. Specifically, the compaction density of the negative electrode active material layer after roller pressing and formation treatment, the compaction density of the negative electrode active material layer when the battery is in a fully charged state or fully discharged state, and the compaction density of the negative electrode active material layer after the battery has been stationary for a long time are all within the aforementioned range.
[0105] As an example, the compaction density of the negative electrode active material layer may be 1.65 g / cm 3 , 1.70g / cm 3 , 1.75g / cm 3, 1.80g / cm 3 or 1.85g / cm 3 .
[0106] It should be noted that the compaction density of the negative electrode active material layer is the designed compaction density after roller pressing. After the battery has undergone charge and discharge cycles, the negative electrode active material will expand due to the insertion of lithium ions, causing the negative electrode active material layer to rebound, thereby reducing the compaction density of the negative electrode active material layer. For example, when the designed compaction density of the negative electrode active material layer after roller pressing is 1.65 g / cm 3 -1.85g / cm 3 When the negative electrode active material layer is subjected to charge and discharge cycles, the compact density may be 1.55 g / cm 3 -1.75g / cm 3 .
[0107] In some embodiments, the surface density of the negative electrode active material layer may be greater than or equal to 7 mg / cm 2 , for example, it can be 8 mg / cm 2 -15mg / cm 2 .
[0108] As an example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is disposed on any one or both of the two facing surfaces of the negative electrode current collector.
[0109] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0110] In some embodiments, in addition to the aforementioned negative electrode active materials, the negative electrode active material layer may also contain negative electrode active materials for batteries known in the art.
[0111] As an example, the negative electrode active material may also include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Silicon-based materials include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials include at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0112] In some embodiments, the negative electrode active material layer may further include a binder, which may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0113] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0114] In some embodiments, the negative electrode active material layer may further include other auxiliary agents, such as a dispersant (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0115] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0116] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, metal active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent short circuits between the positive and negative electrodes, while allowing metal active ions to pass through.
[0117] [Positive electrode]
[0118] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.
[0119] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0120] In some embodiments, when the battery is a lithium ion battery, the positive electrode active material may be a positive electrode active material for lithium ion batteries known in the art.
[0121] As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05O2) and its modified compounds. Examples of lithium-containing phosphates with olivine structure may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. The modified compounds of the above materials may be doping modification and / or surface coating modification of the materials.
[0122] The battery will be accompanied by Li insertion, extraction and consumption during the charging and discharging process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after the charge and discharge cycle.
[0123] In the list of positive electrode active materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0124] In some embodiments, the positive electrode active material layer may further optionally include a binder.
[0125] As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0126] In some embodiments, the positive active material layer may further optionally include a conductive agent.
[0127] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0128] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0129] [Electrolytes]
[0130] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0131] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0132] In some embodiments, the electrolyte salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0133] In some embodiments, the solvent includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0134] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0135] In some embodiments, the battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0136] [Isolation film]
[0137] In some embodiments, the material of the isolation membrane includes at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0138] The battery of the present application includes a battery cell form, a battery module form and a battery pack form. The battery cell, battery module and battery pack of the present application are described below with reference to the accompanying drawings as appropriate.
[0139] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by a winding process or a lamination process.
[0140] In some embodiments, the battery may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0141] In some embodiments, the outer packaging of the battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, for example, may include polypropylene, polybutylene terephthalate, polybutylene succinate, etc.
[0142] The present application has no particular limitation on the shape of the battery, which may be cylindrical, square or any other shape. Figure 2 The battery cell 5 is a square structure as an example.
[0143] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell can be one or more, and those skilled in the art can select according to specific actual needs.
[0144] In some embodiments, batteries may be assembled into a battery module. The number of batteries contained in the battery module may be one or more. The specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0145] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0146] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0147] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0148] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0149] In the second aspect of the present application, the present application proposes an electric device, comprising the aforementioned lithium-ion secondary battery. Therefore, the electric device has all the characteristics and advantages of the aforementioned battery, which will not be described in detail here.
[0150] Batteries, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.
[0151] As an electrical device, a battery, a battery module or a battery pack can be selected according to its usage requirements.
[0152] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of the battery, a battery pack or a battery module can be used.
[0153] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery may be used as a power source.
[0154] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0155] Example 1
[0156] The negative electrode sheet preparation process is as follows:
[0157] Preparation of the first negative electrode slurry: Take the first negative electrode active material, the conductive agent conductive carbon, the stabilizer sodium carboxymethyl cellulose and the binder SBR in a mass ratio of 96.5:0.4:1.1:2.0 and disperse them in deionized water to form a negative electrode slurry, wherein the oil absorption value of the first negative electrode active material is 45ml / 100g, the primary particles account for 90%, and the Dv50 particle size is 16μm.
[0158] Preparation of the second negative electrode slurry: The second negative electrode active material, conductive carbon, stabilizer sodium carboxymethyl cellulose and binder SBR are dispersed in deionized water in a mass ratio of 97.3:0.7:1.2:0.8 to form a negative electrode slurry, wherein the oil absorption value of the second negative electrode active material is 47 ml / 100 g, the number of secondary particles accounts for 70%, and the Dv50 particle size is 13 μm.
[0159] Preparation of negative electrode sheet: The first negative electrode slurry and the second negative electrode slurry are evenly coated on both sides of the negative electrode current collector copper foil by an extrusion coater, and the coating weight of the upper and lower layers is controlled to be 0.076g / 1540mm 2 and 0.114g / 1540mm 2 , dried in an oven, and then compacted using a cold press, with the density controlled at 1.7g / cm 3 The thickness H1 of the first negative electrode active material layer is 30 μm, the thickness H2 of the second negative electrode active material layer is 45 μm, and the ratio of H1:H2 is 2:3.
[0160] Example 2
[0161] Example 2 is consistent with Example 1, except that the oil absorption value and the proportion of secondary particles of the first negative electrode active material are 60 ml / 100 g and 70% respectively, and the oil absorption value and the proportion of secondary particles of the second negative electrode active material are 62 ml / 100 g and 80% respectively.
[0162] Example 3
[0163] Example 3 is consistent with Example 1, except that the oil absorption value and the proportion of secondary particles of the first negative electrode active material are 52 ml / 100 g and 80% respectively, and the oil absorption value and the proportion of secondary particles of the second negative electrode active material are 55 ml / 100 g and 72% respectively.
[0164] Example 4
[0165] Example 4 is consistent with Example 3, except that the thickness H1 of the first negative electrode active material layer and the thickness H2 of the second negative electrode active material layer are 2:1.
[0166] Example 5
[0167] Example 5 is consistent with Example 3, except that the thickness H1 of the first negative electrode active material layer and the thickness H2 of the second negative electrode active material layer are 4:1.
[0168] Example 6
[0169] Example 6 is consistent with Example 3, except that the particle sizes Dv50 of the first negative electrode active material and the second negative electrode active material are 14 μm and 12 μm, respectively.
[0170] s
[0171] Example 7
[0172] Example 7 is consistent with Example 3, except that the particle sizes Dv50 of the first negative electrode active material and the second negative electrode active material are 16 μm and 15 μm, respectively.
[0173] Comparative Example 1
[0174] Comparative Example 1 is consistent with Example 1, except that only the first negative electrode slurry is used to form the negative electrode active material layer.
[0175] Comparative Example 2
[0176] Comparative Example 2 is consistent with Example 1, except that only the second negative electrode slurry is used to form the negative electrode active material layer.
[0177] Comparative Example 3
[0178] Comparative Example 3 is consistent with Example 1, except that the second negative electrode active material layer is located on the surface of the negative electrode current collector, and the first negative electrode active material layer is located on the side of the second negative electrode active material layer away from the current collector.
[0179] Assembling the aforementioned negative electrode sheets into a battery specifically includes:
[0180] Positive electrode sheet: Take positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent Super-P, and binder polyvinylidene fluoride were dispersed in N-methylpyrrolidone in a mass ratio of 97.4:1.5:1.1 to prepare positive electrode slurry, which was then coated on the positive electrode current collector aluminum foil with a coating weight of 0.302 g / 1540 mm 2 After being compacted by a cold press, it is further cut to obtain the positive electrode sheet. The compaction density of the positive electrode sheet is 3.45g / cm 3 .
[0181] Separator: A polyethylene porous membrane with a thickness of 12 μm was selected.
[0182] Electrolyte: At 25°C, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain a mixed solvent, and then LiPF6 was dissolved in the mixed solvent to obtain an electrolyte, in which the concentration of LiPF6 was 1 mol / L.
[0183] Battery assembly: stack the prepared negative electrode sheet, separator, and positive electrode sheet in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and wind them to obtain a bare battery cell, which is then inserted into the battery casing. After baking, liquid injection, standing, packaging, formation, and capacity division, the battery is obtained.
[0184] The batteries in the above examples and comparative examples were tested as follows. The test results are shown in Table 1:
[0185] Test of 25℃ fast charging capability: The prepared battery was placed at room temperature of 25℃, charged to 4.25V with a constant current of 0.33C, then charged at a constant voltage to a current of 0.05C, left for 5 minutes, and then discharged to 2.5V with a constant current of 0.33C. The constant current discharge capacity was recorded as the initial capacity C0. The battery was charged with a constant current of 0.5C0, 1C0, 1.5C0, 2C0, 2.5C0, 3C0, and 3.5C0 in sequence to a full battery potential of 4.25V or a negative electrode cutoff potential of 0mV (achieving any one of these conditions indicates that charging is complete), and discharged to 2.5V with 0.33C0 after each charge. At every interval of 10% SOC (from 10% SOC-80% SOC), the corresponding negative electrode potential at different charging rates was recorded, and the rate-negative electrode potential curve at different SOCs was drawn. After linear fitting, the charging rate corresponding to the negative electrode potential of 0mV at different SOCs was obtained, recorded as C x (x=2-8). According to the formula (1 / C2+1 / C3+1 / C4+1 / C5+1 / C6+1 / C7+1 / C8)×0.1×60, the charging time T (min) for charging the battery from 10% SOC to 80% SOC is calculated. The shorter the time, the better the fast charging performance of the battery.
[0186] Capacity retention rate: At 25°C, charge the battery at a constant current of 0.33C to a charge cut-off voltage of 4.25V, then charge at a constant voltage to a current of 0.05C, let stand for 5 minutes, and then discharge at a constant current of 0.33C to a discharge cut-off voltage of 2.5V, and record its initial capacity as C0. Then charge according to the charging strategy described above, and discharge at 0.33C0, and record the discharge capacity C0 of each cycle. n (n is the number of cycles, n is 1-1000), until the 1000th cycle, calculate the cycle capacity retention rate (i.e. C 1000 / C0×100%). The higher the cycle retention rate, the better the life.
[0187] Table 1
[0188] serial number Fast charging performance / min Capacity retention rate / % Example 1 20 87.5 Example 2 18 88.6 Example 3 17 90.7 Example 4 16 91.4 Example 5 19 88.1 Example 6 16.2 91.5 Example 7 17.9 89.9 Comparative Example 1 25 80.1 Comparative Example 2 30 75.3 Comparative Example 3 34 69.5
[0189] The test results show that the fast charging performance and cycle performance of the batteries in Examples 1 to 7 are better than those in the comparative examples. Specifically, the first negative electrode active material layer of the batteries in Examples 1 to 7 can provide more lithium insertion and extraction sites, and the second negative electrode active material layer can provide fast lithium insertion and extraction channels, which are conducive to the rapid insertion of lithium ions and improve the fast charging performance of the negative electrode sheet. As a result, the batteries have better fast charging performance and better cycle performance.
[0190] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lithium ion secondary battery, characterized in that: include: A negative electrode plate, the negative electrode plate comprising: Anode current collector; A negative electrode active material layer, the negative electrode active material layer comprising a first negative electrode active material layer and a second negative electrode active material layer stacked, the second negative electrode active material layer being located on a side of the first negative electrode active material layer away from the negative electrode current collector, wherein: The first negative electrode active material layer includes a first negative electrode active material, the first negative electrode active material includes graphite, and the amount of primary particles in the first negative electrode active material accounts for a greater proportion than the amount of secondary particles; The second negative electrode active material layer includes a second negative electrode active material, the second negative electrode active material includes graphite, and the number of secondary particles in the second negative electrode active material is greater than the number of primary particles.
2. The lithium ion secondary battery according to claim 1, characterized in that: The number of primary particles in the first negative electrode active material accounts for greater than or equal to 70%, and the oil absorption value of the first negative electrode active material is 45 mL / 100 g-60 mL / 100 g.
3. The lithium ion secondary battery according to claim 1 or 2, characterized in that: The amount of secondary particles in the second negative electrode active material accounts for greater than or equal to 70%, and the oil absorption value of the second negative electrode active material is greater than the oil absorption value of the first negative electrode active material.
4. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that: The oil absorption value of the second negative electrode active material is 47 mL / 100 g to 62 mL / 100 g.
5. The lithium ion secondary battery according to any one of claims 1 to 4, characterized in that: The Dv50 particle size of the second negative electrode active material is smaller than the Dv50 particle size of the first negative electrode active material.
6. The lithium ion secondary battery according to claim 5, characterized in that: The Dv50 particle size of the first negative electrode active material is 14 μm-22 μm, and / or the Dv50 particle size of the second negative electrode active material is 12 μm-19 μm.
7. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: The thickness of the first negative electrode active material layer is H1, the thickness of the second negative electrode active material layer is H2, and the ratio of H1 to H2 is in the range of (2:3)-(4:1).
8. The lithium ion secondary battery according to claim 7, characterized in that: H1 is 30μm-90μm, and H2 is 20μm-60μm.
9. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that: The specific surface area of the second negative electrode active material is greater than the specific surface area of the first negative electrode active material.
10. The lithium ion secondary battery according to any one of claims 1 to 9, characterized in that: Under a pressure of 50000N, the compaction density of the first negative electrode active material is greater than the compaction density of the second negative electrode active material.
11. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: The powder OI value of the second negative electrode active material is smaller than the OI value of the first negative electrode active material.
12. The lithium ion secondary battery according to any one of claims 1 to 11, characterized in that: The gram capacity of the first negative electrode active material is greater than the gram capacity of the second negative electrode active material.
13. The lithium ion secondary battery according to any one of claims 1 to 12, characterized in that: The second negative electrode active material includes the secondary particle with a carbon coating layer, wherein the carbon coating layer is located at least on a portion of the surface of the secondary particle, and the secondary particle is formed by bonding at least two primary particles, and the bonding material includes a carbon material.
14. The lithium ion secondary battery according to any one of claims 1 to 13, characterized in that: The compaction density of the negative electrode active material layer is 1.65 g / cm 3 -1.85g / cm 3 .
15. An electrical device, characterized in that: A lithium ion secondary battery comprising any one of claims 1 to 14.
Citation Information
Patent Citations
Secondary battery and electronic device
CN116544350A
Graphite negative electrode active material, negative electrode pole piece, secondary battery and device
CN117712376A
Battery, preparation method thereof and power utilization device
CN118263401A
Negative electrode active material, non-aqueous electrolyte secondary battery, and method of producing negative electrode active material
US20240222627A1
Cited By
Battery cell of lithium ion battery, lithium ion battery and power utilization device
CN121076247A
A negative electrode sheet manufacturing method, a negative electrode sheet, and a lithium ion battery manufacturing method
CN122532169A
Lithium-ion secondary battery and electric apparatus
WO2026144200A1